2003
DOI: 10.1164/rccm.200305-628oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Surface Liquid Calcium Modulates Chloride Permeability in the Cystic Fibrosis Airway

Abstract: Patients with cystic fibrosis (CF) demonstrate a characteristic defect in epithelial chloride movement, which can be demonstrated in vivo by the nasal potential difference technique. After amiloride pretreatment, the CF airway exhibits only a transient response to perfusion with low-chloride solution, contrasting with the sustained hyperpolarization seen in control subjects. This study further investigated the response to low-chloride solution in the CF airway, examining the interaction between surface divalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…There are two possible explanations for the relatively large change in PD associated with a reduction in luminal Cl ¡ concentration in CF: (1) The solutions used in our study to superfuse the respiratory epithelium did not contain Ca 2+ and Mg 2+ . It has been shown that solutions lacking these divalent ions lead to a larger change in PD associated with a reduction in luminal Cl ¡ concentration compared with solutions containing Ca 2+ and Mg 2+ (Middleton et al 2003). This eVect might result from an increase in the open probability of tight junctions induced by a reduction in extracellular Ca 2+ concentration (Gorodeski et al 1997), thereby promoting Cl ¡ Xux to the luminal side of the epithelium if apical Cl ¡ concentration is low.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible explanations for the relatively large change in PD associated with a reduction in luminal Cl ¡ concentration in CF: (1) The solutions used in our study to superfuse the respiratory epithelium did not contain Ca 2+ and Mg 2+ . It has been shown that solutions lacking these divalent ions lead to a larger change in PD associated with a reduction in luminal Cl ¡ concentration compared with solutions containing Ca 2+ and Mg 2+ (Middleton et al 2003). This eVect might result from an increase in the open probability of tight junctions induced by a reduction in extracellular Ca 2+ concentration (Gorodeski et al 1997), thereby promoting Cl ¡ Xux to the luminal side of the epithelium if apical Cl ¡ concentration is low.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal PD was measured using previously described methods. 3,12,13 Briefly, the exploring electrode consisted of a double lumen silicone rubber tube with the openings of both lumens at the same site, 3 mm from the tip. One lumen was filled with an equal mixture of saline and ECG electrode cream, connected to a high impedance voltmeter via a silver/silver chloride electrode.…”
Section: Nasal Pd Measurementsmentioning
confidence: 99%
“…The nasal PD test provides important information to assist in the diagnosis of CF, especially in cases where the sweat test and genotype analysis are non‐diagnostic 5. The nasal PD has been used to assess the epithelial effects of current treatments 6, 7, to test the efficacy of potential new drugs for CF 8, 9, and also to investigate the physiology of the ion transport defects in CF 10, 11.…”
Section: Introductionmentioning
confidence: 99%